High Glucose Impairs Early and Late Endothelial Progenitor Cells by Modifying Nitric Oxide–Related but Not Oxidative Stress–Mediated Mechanisms - Chen, Yung-Hsiang; Lin, Shing-Jong; Lin, Feng-Yen; Wu, Tao-Cheng; Tsao, Chen-Rong; Huang, Po-Hsun; Liu, Po-Len; Chen, Yuh-Lien; Chen, Jaw-Wen (Diabetes (New York, N.Y.), 2007)
High Glucose Impairs Early and Late Endothelial Progenitor Cells by Modifying Nitric Oxide–Related but Not Oxidative Stress–Mediated Mechanisms Yung-Hsiang Chen 1 2 3 , Shing-Jong Lin 1 2 4 , Feng-Yen Lin 1 4 , Tao-Cheng Wu 1 2 4 , Chen-Rong Tsao 1 5 , Po-Hsun Huang 1 2 4 , Po-Len Liu 6 , Yuh-Lien Chen 7 and Jaw-Wen Chen 1 2 4 1 School of Medicine, National Yang-Ming University, Taipei City, Taiwan 2 Cardiovascular Research Center, National Yang-Ming University, Taipei City, Taiwan 3 Graduate Institute of Integrated Medicine, China Medical University, Taichung, Taiwan 4 Division of Cardiology, Department of Medicine, National Taipei Veterans General Hospital, Taipei City, Taiwan 5 Taichung Veterans General Hospital, Taichung, Taiwan 6 Faculty of Respiratory Care, Kaohsiung Medical University, Kaohsiung, Taiwan 7 Department of Anatomy and Cell Biology, National Taiwan University, Taipei, Taiwan Address correspondence and reprint requests to Jaw-Wen Chen, MD, Division of Cardiology, Department of Medicine, Taipei Veterans General Hospital, No. 201, Sec. 2, Shih-Pai Road, Taipei 112, Taiwan. E-mail: jwchenatvghtpe.gov.tw Abstract OBJECTIVE—Endothelial progenitor cells (EPCs) are impaired in diabetes. This study aimed to investigate the direct effects of high glucose on EPCs. RESEARCH DESIGN AND METHODS—Mononuclear cells isolated from healthy subjects were incubated with glucose/mannitol or drugs for EPC study. After 4 days of culture, attached early EPCs appeared. The monolayer late EPCs with cobblestone shape appeared at 2–4 weeks. Various immunofluroscence stainings were used to characterize the early and late EPCs. Senescence assay and the activity of endothelial nitric oxide synthase (eNOS) were determined. Migration and tube formation assay were done to evaluate the capacity for vasculogenesis in late EPCs. RESULTS—Chronic incubation with high glucose but not mannitol (osmotic control) dose-dependently reduced the number and proliferation of early and late EPCs, respectively. High glucose enhanced EPC senescence and impaired the migration and tube formation of late EPCs. High glucose also decreased eNOS, FoxO1, and Akt phosphorylation and bioavailable nitric oxide (NO) in both EPCs. The effects of high glucose could be ameliorated by coincubation with NO donor sodium nitroprusside or p38 mitogen–activated protein kinase inhibitor and deteriorated by eNOS inhibitor or PI3K (phosphatidylinositol 3′-kinase) inhibitor. Antioxidants including vitamin C, N -acetylcysteine–and polyethylene glycol (PEG)-conjugated superoxide dismutase, and PEG-catalase had no effects, whereas pyrrolidine dithiocarbamate, diphenyleneiodonium, apocynin, and rotenone even deteriorated the downregulation of both EPCs. CONCLUSIONS—High glucose impaired the proliferation and function of early and late EPCs. NO donor but not antioxidants reversed the impairments, suggesting the role of NO-related rather than oxidative stress–mediated mechanisms in hyperglycemia-caused EPC downregulation. acLDL, acetylated LDL DiI-acLDL, 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindocarbocyanine–labeled acLDL eNOS, endothelial nitric oxide synthase EPC, endothelial progenitor cell l-NAME, l-Ng-nitro-l-arginine methyl ester MAPK, mitogen-activated protein kinase MNC, mononuclear cell PEG, polyethylene glycol MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide ROS, reactive oxygen species VEGF, vascular endothelial growth factor UEA-1, ulex europaeus agglutinin Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 26 March 2007. DOI: 10.2337/db06-1103. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted March 12, 2007. Received August 8, 2006. DIABETES